The Vital Role of The Islamic Family In Efforts To Ward Off The Entry of Radicalism In The Family - Handoko Budi Prasetiyo; Umi Sumbulah; Fakhrudin fakhrudin (International Journal Labs, 2024)
Radicalism is a doctrine to someone who is closely related to the jihad phenomenon identified with negative actions. Every so often our societies are confronted with terrorist violence because of radicalization. Therefore, this research wants to focus on the role of the family in preventing radicalism and how can social interaction in the environment affect the entry of radicalism towards children. This research used library research based on the type of current research approach. The findings show that the role of education by family units has a great contribution to the deradicalization process, through the important role of education that can be directly exemplified by the family. In addition to the social interaction channels, interaction in social groups with children and other family members, especially in the context of interaction through the internet, also needs to be considered.